Association of umbilical cord serum TARC/CCL17 with childhood allergies: A birth cohort study - Noriko Sato; Fumiya Yamaide; Taiji Nakano; Syuji Yonekura; Yoshitaka Okamoto; Naoki Shimojo (Allergology International, 2023)
Background: Early identification of infants at high risk of allergies can improve the efficacy of preventive interventions. However, an established quantifiable risk assessment method in the early postnatal period does not exist. TARC (or CCL17) is a Th2 chemokine used as an activity marker for atopic dermatitis (AD). Therefore, we evaluated the association between cord blood TARC (cTARC) and the development of allergic diseases in childhood. Methods: This is a high-risk birth cohort for allergy, consisting of children with a family history of allergy. We collected 263 pairs of maternal and child cord blood samples perinatally and child blood samples at ages 1, 2, and 5 years. TARC and allergen-specific immunoglobulin E levels were measured, and the relationship between allergic diseases was analyzed. Results: The median cTARC was 989 pg/mL (interquartile range [IQR]: 667–1430 pg/mL). The cTARC levels in children who developed AD were higher than those in children who did not develop AD, and the association strengthened with younger age (median [IQR] at 1 year: 1285 [816–1965] vs. 933 [662–1330] pg/mL, p < 0.01; at 2 years: 1114 [787–1753] vs. 950 [660–1373] pg/mL, p = 0.02). In the multivariate analysis, cTARC was associated with AD, egg white sensitization, food allergy, allergic rhinitis, and Japanese cedar pollen sensitization. Conclusions: cTARC was associated with the development of allergic diseases and allergen sensitization in early childhood. These results suggest that, infantile AD-mediated atopic march starts during fetal life, and this immune status is reflected in the cTARC at birth.